2020
DOI: 10.1002/cncr.32850
|View full text |Cite
|
Sign up to set email alerts
|

Medical financial hardship reported by Native Hawaiian and Pacific Islander cancer survivors compared with non‐Hispanic whites

Abstract: BACKGROUND: Although medical financial hardship (MFH) resulting from sequelae of cancer and treatment has been reported in other racial/ethnic populations, little is known about MFH among Native Hawaiian and Pacific Islander (NHPI) cancer survivors. METHODS: One hundred fifty adult NHPI cancer survivors were identified from the 2014 NHPI National Health Interview Survey (NHIS). Cancer survivors were those with a history of cancer (excluding nonmelanoma/unknown type of skin cancer). MFH was defined by 3 domains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…13 Post-treatment, US NHPIs experience disproportionately high financial toxicity, causing major psychological harm. 14 PIs also have a unique cancer contextualization given nuclear bomb testing. During the Cold War, the United States detonated 67 hydrogen bombs on the Marshall Islands, with an aggregate explosion akin to 7,200 Hiroshima bombs.…”
mentioning
confidence: 99%
“…13 Post-treatment, US NHPIs experience disproportionately high financial toxicity, causing major psychological harm. 14 PIs also have a unique cancer contextualization given nuclear bomb testing. During the Cold War, the United States detonated 67 hydrogen bombs on the Marshall Islands, with an aggregate explosion akin to 7,200 Hiroshima bombs.…”
mentioning
confidence: 99%
“…Among the scoped articles, survival disparities, primary care, environmental exposures, quality of life, and residential mobility were the main themes related to surveillance. Neighborhood measures utilized in these articles were: nSES, neighborhood ethnic enclaves [ 36 ], residential segregation [ 37 ], access and travel distance [ 38 ], pharmacy access [ 39 ], food access [ 18 ], social and economic polarization [ 40 ], neighborhood amenities [ 39 ], neighborhood tenure [ 41 ], perceived social cohesion [ 41 , 42 ], and social capital [ 43 ]. nSES was the most common metric and there is abundant literature that shows lower nSES exerts a deleterious effect on cancer outcomes which goes beyond the area supply of specific heath care types [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Across the scoped articles, social support, quality of life, self-rated health, medical and financial hardships, and stress management were the studied themes. Among these reviewed articles, nSES, neighborhood social support [ 22 ], neighborhood social cohesion [ 42 ], perceived neighborhood stress [ 69 ], and housing situation were the neighborhood-level variables under the psychological well-being theme. One study found a strong association between social support and financial circumstances and one or more unmet needs among head and neck cancer survivors [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, Native Hawaiian and Pacific Islanders report greater financial hardship than other Asian subgroups (i.e., Asian Indian, Chinese, Filipino, and Other) and compared to non-Hispanic Whites. 34 Hispanic/Latina women with breast cancer are more likely to report job insecurity and feel cancer significantly impacted their employability than White, Asian, and Black women, whereas Black women are more likely to report economicrelated discrimination as a barrier to care. 35 Unfortunately, it appears that health disparities across races and ethnicities persist even at high income levels, 36,37 suggesting the importance of focusing on financial experiences and health disparities across race/ethnicity subgroups at all socioeconomic strata.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to recognize the varying experiences between and within race and ethnicity subgroups. For example, Native Hawaiian and Pacific Islanders report greater financial hardship than other Asian subgroups (i.e., Asian Indian, Chinese, Filipino, and Other) and compared to non‐Hispanic Whites 34 . Hispanic/Latina women with breast cancer are more likely to report job insecurity and feel cancer significantly impacted their employability than White, Asian, and Black women, whereas Black women are more likely to report economic‐related discrimination as a barrier to care 35 .…”
Section: Discussionmentioning
confidence: 99%